If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = 11 + 2x Reorder the terms: 8 + 3x = 11 + 2x Solving 8 + 3x = 11 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + 3x + -2x = 11 + 2x + -2x Combine like terms: 3x + -2x = 1x 8 + 1x = 11 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + 1x = 11 + 0 8 + 1x = 11 Add '-8' to each side of the equation. 8 + -8 + 1x = 11 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 11 + -8 1x = 11 + -8 Combine like terms: 11 + -8 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 314=13(x-2)-(12x-13)+2(150+x) | | 8t-2=16(t-2.5) | | 2+2y=-6 | | 4x+3=12x-13 | | 1+3x=16-2r | | 6+9x=8x-12 | | 12h=10h | | 3-4x=44 | | 56x+2=42x+5 | | 5-8x=24 | | 4x-25=105 | | 5x-9=13x-(8x-4) | | 2x-4-5x+10=40 | | 3x+17=59 | | 4(2m+1)=3(2m-5) | | 40x+40=15x+30 | | 3x(2x-1)(x^2-9)(x^2+8)=0 | | 5x^2=3y | | 4x=22x+56 | | -8=32-8q | | 10(3-x)-4(6-8x)+1,5(4-10x)-26=0 | | 30-12x=26+4x | | 4t^2+7t-15=0 | | 4(2x-3)=23 | | 12z+7=67+9z | | 4(h-7)+4=-8 | | 2(c+10)-9=7 | | 5t-7+9t=4t-33 | | 6m-2=19-m | | 5(h-1)+6=-9 | | 2(w+5)-1=5 | | -4(s-6)-3=9 |